Wrist-hand extension function recovery in spastic hemiplegia patient by botulinum toxin injection plus surface electromyography biofeedback therapy: A case report. Issue 14 (9th April 2021) - Wu, Zhang-xiang; Wang, Chao; Huang, Zheng; Liu, Xue-han; Shen, Mei
Abstract: Rationale: Wrist-hand extension function rehabilitation is a vital and difficult part of hand function recovery in spastic stroke patients. Although botulinum toxin type A (BoNTA) injection plus post injection therapy was applied to the wrist-hand rehabilitation in previous reports, conclusion was inconsistent in promoting function. For this phenomenon, proper selection of patients for BoNTA injection and correct choice of post-injection intervention could be the crucial factors for the function recovery. Patient concerns: We reported a 46-year-old male suffered a spastic hemiplegia with wrist- hand extension deficit. Diagnoses: Computed tomography showed cerebral hemorrhage in the left basal ganglia region. Interventions: Four hundred units of BoNTA were injected into the spasticity flexors, and four-week post injection surface electromyography (sEMG) biofeedback therapy was applied to the patient. Outcomes: The patient exhibited post-intervention improvement in wrist-hand extensors performance (strength, range of motion, sEMG signals), the flexors spasticity, and upper extremity function. Lessons: The present case showed that 4-week of BoNTA injection plus sEMG biofeedback exercise improved the performance and function of wrist-hand extensors in the patient for short- and long-term. Proper selection of patients for BoNTA injection and correct choice of post injection exercise could play a vital role in the hand rehabilitation for patient with spastic hemiplegia.